Developing a Social Media Intervention to Connect Alaska Native People Who Smoke with Resources and Support to Quit Smoking: The Connecting Alaska Native Quit Study. Issue 6 (2nd December 2020) - Merculieff, Zoe T; Koller, Kathryn R; Sinicrope, Pamela S; Hughes, Christine A; Bock, Martha J; Decker, Paul A; Resnicow, Kenneth; Flanagan, Christie A; Meade, Crystal D; McConnell, Clara R; Prochaska, Judith J; Thomas, Timothy K; et al.
Abstract: Background: Face-to-face tobacco cessation has had limited reach and efficacy in Alaska Native (AN) communities. We describe our two-phased approach to develop content for Connecting Alaska Native People to Quit Smoking, a Facebook group intervention to reduce barriers to evidence-based smoking cessation treatment for AN people in Alaska. Methods: Phase 1 included semi-structured telephone interviews with 30 AN people who smoke and ten stakeholders. They provided feedback on existing content from the Centers for Disease Control and Prevention Tips campaign and AN digital stories. Phase 2 included an online survey with a new group of 40 AN smokers who provided feedback on existing content via a measure of perceived effectiveness and cultural relevance. Results: Phase I results revealed participants evaluated content based upon story strength, relevance to AN culture, emotional appeal, relatability to AN people, and favorite video. No single posting was rated highly across all themes. All perceived effectiveness (PE) and cultural relevance median scores fell between 3.5 and 4.4 (range 1–5). PE scores varied across participant demographic groups. Conclusions: Content embodying characteristics perceived to be most appealing, effective, and culturally relevant were selected for the private Facebook group content library with refinements made to incorporate images of AN people engaged in AN activities. PE scores indicate a need for a wide variety of content that moderators could pull from when conducting the intervention. Implications: Social media content targeting specific population sectors, such as American Indian/AN people for tobacco cessation needs to be culturally tailored. Our approach provides a model others can follow to determine what is appealing, relevant, and effective messaging. Clinical Trial Registration: NCT 03645941.